Effect of panretinal photocoagulation on the peripapillary retinal nerve fiber layer in diabetic retinopathy patients - Leandro Cabral Zacharias; Breno M.S. Azevedo; Rafael B. de Araujo; Marina R. Ciongoli; Marcelo Hatanaka; Rony C. Preti; Mario Luiz Ribeiro Monteiro (Clinics)
OBJECTIVES: To determine the effect of panretinal photocoagulation (PRP) on the peripapillary retinal nerve fiber layer (RNFL) in nonglaucomatous patients with proliferative diabetic retinopathy (PDR). METHODS: This is a prospective, single center, observational study. Thirty-eight eyes of 26 diabetic patients underwent PRP for proliferative diabetic retinopathy. Peripapillary RNFL thickness was measured using scanning laser polarimetry (SLP) with variable corneal compensation (GDx VCC; by Carl Zeiss Meditec, Dublin, CA) and spectral-domain optical coherence tomography (OCT) (Heidelberg Spectralis, Carlsbad, USA) at baseline and 12 months after PRP was performed. RESULTS: Thirty-eight eyes of 26 patients (15 female) with a mean age of 53.7 years (range 26 to 74 years) were recruited. No significant difference was found among all RNFL thickness parameters tested by GDx VCC software (p=0.952, 0.464 and 0.541 for temporal-superior-nasal-inferior-temporal (TSNIT) average, superior average, inferior average, respectively). The nerve fiber indicator (NFI) had a nonsignificant increase (p=0.354). The OCT results showed that the average RNFL thickness (360° measurement) decreased nonsignificantly from 97.2 mm to 96.0 mm at 1 year post-PRP (p=0.469). There was no significant difference when separately analyzing all the peripapillary sectors (nasal superior, temporal superior, temporal, temporal inferior, nasal inferior and nasal thickness). CONCLUSION: Our results suggest that PRP, as performed in our study, does not cause significant changes in peripapillary RNFL in diabetic PDR patients after one year of follow-up.